2002
DOI: 10.1002/jclp.10054
|View full text |Cite
|
Sign up to set email alerts
|

Prescription privileges for psychologists: Constituencies and conflicts

Abstract: The pros and cons of the proposal to link prescription privileges specifically to psychological training vary from the point of view of the constituencies involved. The present article analyzes those differences. Two surprising facts are noted. First, it is scientist-practitioners who are resisting the move toward prescription privileges, not so much the basic science organizations. Second, while the practice-based organizations have been avid in their support of prescription privileges, the same cannot be sai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
25
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 2 publications
10
25
0
Order By: Relevance
“…There has been a mass devaluation of ISE by all helping professions, not just counseling. The primary political agenda of the psychology profession, for example, is to gain prescription privileges (e.g., Hayes, Walser, & Bach, 2002). If counselors resist this trend toward medicalization and, instead, refocus their efforts on ISE, this would create a standout, and sorely needed, professional identity in the contemporary mental health marketplace.…”
Section: Social Constructionismsupporting
confidence: 41%
“…There has been a mass devaluation of ISE by all helping professions, not just counseling. The primary political agenda of the psychology profession, for example, is to gain prescription privileges (e.g., Hayes, Walser, & Bach, 2002). If counselors resist this trend toward medicalization and, instead, refocus their efforts on ISE, this would create a standout, and sorely needed, professional identity in the contemporary mental health marketplace.…”
Section: Social Constructionismsupporting
confidence: 41%
“…They inevitably would have a major negative impact on both the substance and quality of scientific training in clinical psychology. 4 Opponents of PPP legislation have provided a long list of reasons why this is a bad idea (see American Psychologist, 1996;Hayes & Heiby, 1998). I agree with these reasons.…”
supporting
confidence: 42%
“…The RÂP proposal remains controversial within psychology and objections involve anticipated negative effects of the amount of training (Albee, 2002;Bush, 2002;Hayes & Heiby, 1996, 1998Hayes, Walser, & Bach, 2002;Heiby, 2002;Heiby et al, 2004;McFall, 2002;Pollitt, 2003;Sechrest & Coan, 2002;Wagner, 2002). Proponents of RÂP have observed that the major reason for the failure of most enabling legislation is concern over the quality of the APA model training (Fox et al, 2009), and the consumer protection reasons given in one governor's veto of an enabling bill supports this impression (Lingle, 2007).…”
Section: Context Of Evaluating Râp Trainingmentioning
confidence: 40%